How deep is the conflict between molecular and fossil evidence on the age of angiosperms?. Issue 1 (26th February 2019) - Coiro, Mario; Doyle, James A.; Hilton, Jason
Summary: The timing of the origin of angiosperms is a hotly debated topic in plant evolution. Molecular dating analyses that consistently retrieve pre‐Cretaceous ages for crown‐group angiosperms have eroded confidence in the fossil record, which indicates a radiation and possibly also origin in the Early Cretaceous. Here, we evaluate paleobotanical evidence on the age of the angiosperms, showing how fossils provide crucial data for clarifying the situation. Pollen floras document a Northern Gondwanan appearance of monosulcate angiosperms in the Valanginian and subsequent poleward spread of monosulcates and tricolpate eudicots, accelerating in the Albian. The sequence of pollen types agrees with molecular phylogenetic inferences on the course of pollen evolution, but it conflicts strongly with Triassic and early Jurassic molecular ages, and the discrepancy is difficult to explain by geographic or taphonomic biases. Critical scrutiny shows that supposed pre‐Cretaceous angiosperms either represent other plant groups or lack features that might confidently assign them to the angiosperms. However, the record may allow the Late Jurassic existence of ecologically restricted angiosperms, like those seen in the basal ANITA grade. Finally, we examine recently recognized biases in molecular dating and argue that a thoughtful integration of fossil and molecular evidence could help resolve these conflicts.